PENGARUH PEMANFAATAN MEDIA VIDEO BIMBINGAN PRAKTIKUM TERHADAP PENINGKATAN HASIL BELAJAR MATERI ORGANISASI KEHIDUPAN DI SMP - Yessi Andriani Sotalapa; Tomo Djuddin; Aloysius Mering (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis research aims to know the influence of using practical guide video media to increase students’ science achievement on organization life materials of the class VII students of Gembala Baik Pontianak. The method used in the study is Quasi Experiment with pretest-posttest control group design. The population is the class VII students of Gembala Baik Pontianak sample VIIB  as experimental class and VIIA control class. The result of research shows average posttest experimental class is 80,13, while the average posttest control class is 73,47. Based on the U Mann-Whitney test with significance level α = 5% indicated there were differences between students that taught by using practical guide video media with students taught by using conventional media. The value of effect size is 1,03 with high category it means practical guide video media gave effect on students learning outcomes.Keywords: Practical Guide Video Media, Students’ Achievement, Life Organization